Microstructure and Properties of Polymer Composites - Hajsman, Jan; Jenicek, Stepan; Kucerova, Ludmila; Rieger, David (Manufacturing Technology Journal, 2019)
This work aimed to characterise microstructure and mechanical properties of polymer composite samples. The main task was to adapt the well-known techniques of metallography (i.e. sample preparation and microscopic examination) to documentation of multi-component polymer materials and to optimize the methods of light and electron microscopy for this particular purpose. There were several issues (e.g. low melting point, absence of electrical conductivity), which made the process different from metal samples preparation and observation and which needed to be addressed. Various mounting resins were tested for the samples to find the suitable one, then the process of grinding and polishing was optimized and finally the microstructure was documented using light and scanning electron microscopy (SEM). Samples in the undeformed state were examined as well as the samples subjected to tensile test at different temperatures. Prior to the microscopic observations the material was analysed using methods of thermal analysis (TG A, DSC) and infrared spectroscopy (FT-IR). The tensile tests were employed not only to determine the mechanical properties but also to obtain deformed samples for further microscopic observation.
Keywords: polymer composites; microscopy; metallography; thermal analysis; tensile test